Development and Validation of the Spirituality Questionnaire among University Students in Higher Educational Centers of Sanandaj in 2017 - Ata Shakerian; Yahya Maroofi; Faezeh Nateghi (Shahid Beheshti University of Medical Sciences, 2020)
For downloading the full-text of this article please click here. Background and Objective: As universal concept that generally denotes a connection with a transcendental power and specifically defined as a search for finding a purpose in life, spirituality has gained attention in academic, educational, and cultural areas more than before. Therefore, it is a necessity to design and use the proper tools to measure this phenomenon. This study aims to develop and validate a questionnaire to "measure spirituality" among university students. Methods: This is a descriptive-analytical study with a statistical society of 464 university students in Sanandaj province. The research tools include a demographic and a spirituality questionnaire. Data analysis involved a two-phase approach including an exploratory factor analysis using principal components analyses method via varimax rotation approach, and confirmatory factor analysis using structural equation modeling. In this study, all the ethical considerations were observed and the authors reported to conflicts of interest. Results: The results of Exploratory factor analysis pointed to the existence of two main dimensions named spiritual experiences and religious experiences which explained 56% of the variance in the spirituality questionnaire. Cronbach alpha coefficient for the dimensions confirmed in factor analysis including spirituality experiences and religious experiences and for the whole questionnaire was 0/88, 0/90, and 0/92, respectively. Convergent validity of the spirituality questionnaire, measured by Parsian and Dunning Spirituality questionnaire, was 0/66. Conclusion: The findings indicated that, Goodness of Fit Index (GFI) of this model is acceptable and could be used as a reliable tool in measurement of university students' spirituality scale, health psychology, and spirituality well-being. For downloading the full-text of this article please click here. Please cite this article as: Shakerian A, Maroofi Y, Nateghi F. Development and Validation of the Spirituality Questionnaire among University Students in Higher Educational Centers of Sanandaj in 2017. Journal of Pizhūhish dar dīn va salāmat. 2020;6(1):100-115. https://doi.org/10.22037/jrrh.v6i1.21301